POSTRZEGANIE OTOCZENIA INSTYTUCJONALNEGO W POLSCE W LATACH 1997-2009 - Kowalski, Tadeusz (Wydział Prawa i Administracji UAM, 2011)
Celem artykułu jest prezentacja i ocena zmian percepcji środowiska instytucjonalnego, ograniczonego w niniejszym opracowaniu do sfery instytucji publicznych, oraz stanowienia i egzekwowania prawa w Polsce w latach 1998-2009. Jakość rozwiązań instytucjonalnych i funkcjonowania otoczenia biznesu w Polsce jest przedmiotem krytyki zarówno ze strony obywateli, przedsiębiorców, jak i polityków. Względnie niskie oceny jakości otoczenia instytucjonalnego wywierają negatywny wpływ na międzynarodową konkurencyjność Polski, i to zarówno w ocenie polskich obserwatorów, jak i zagranicznych partnerów gospodarczych. Analizowany obraz oceny i kierunku zmian w otoczeniu instytucjonalnym oparty jest na własnych badaniach prowadzonych systematycznie na celowo dobranej grupie menedżerów średniego i wyższego szczebla. Tłem dla tak rozumianej analizy jakości i funkcjonowania instytucji publicznych, procedur stanowienia i egzekwowania prawa są zmiany wynikające z wyborów parlamentarnych.

*The aim of this paper is to present and assess the results of surveys into perceptions of shifts in the Polish institutional framework. The author’s empirical research was carried out in Poland during the years 1997-2009 and was focused on three key areas of the institutional environment, namely the functioning of government agencies, the law making and the law enforcement. The paper is divided into Introduction, three main Sections and Conclusion. The second Section is devoted to the presentation of the political scene and parliamentary elections in Poland in the years 1989-2009. The next Section presents the dynamics of law making in Poland and its fluctuations over the terms of parliament. Section four contains an analysis and assessment of the changes in perception of the functioning of government agencies, the law making and law enforcement. It ends with an assessment of the general uncertainty in these three key areas. The Conclusion contains a summary of the considerations and assessments drawn from both quantitative and qualitative analyses of the descriptive and statistical materials.
PERCEPTIONS OF INSTITUTIONAL ENVIRONMENT IN POLAND BETWEEN 1997-2009
Keywords: Instytucje publiczne; Government agencies; Stanowienie prawa; Law making; Egzekwowanie prawa; Law enforcement; Otoczenie instytucjonalne; Institutional environment; Niepewność; Uncertainty; Polska gospodarka; Polish economy; Konkurencyjność; Competitiveness